A new look on performance of small-cell network with design of multiple antennas and full-duplex - Chi-Bao Le; Dinh-Thuan Do (Bulletin of Electrical Engineering and Informatics, 2021)
A downlink of small-cell network is studied in this paper studies in term of outage performance. We beneﬁt by design of multiple antennas at the base station and fullduplex transmission mode. The scenario of multiple surrounded small-cell networks is considered to look the impact of interference. We derive the closed-form expression of outage probability to show performance of mobile user. We investigate target rate is main factor affecting to outage performance. According to the considered system, simulation results indicate reasonable value of outage probability and throughput as well. Finally, Monte-Carlo simulation method is deployed to determine exactness of main results found in this article. Finally, the considered system can exhibit improved performance if controlling interference term.